Antennal morphology and micro‐sensory architecture of the New Zealand magpie moth, Nyctemera annulata (Lepidoptera: Erebidae): diversity, distribution and dimorphism. Issue 3 (10th June 2017) - Mark, Cassandra J; Parsons, Stuart; Holwell, Gregory I
Abstract: Insects rely on chemical information obtained from their surroundings when locating biologically important resources. Detection of these chemicals is mediated by the antennae, which are endowed with various sensory structures called sensilla. Sensilla type, distribution and density vary among species, between sexes and at different life stages, and may provide important information regarding the ability of individuals to detect and process such external stimuli. The aim of this study was to quantitatively investigate the sensory architecture of larval and adult antennae in the New Zealand magpie moth, Nyctemera annulata (Arctiinae) . Using scanning electron microscopy the sensilla were identified and classified into 8 types: trichoid, basiconic, chaetic, auricillic, squamiform, styloconic, coeloconic and Böhm's bristles, with multiple subtypes. Larval antennae were found to possess morphology and sensory structures which are essentially ubiquitous across the Lepidoptera. Sexual dimorphism was apparent in the overall antennal morphology as well as in the distribution, density and morphology of particular types of sensilla in adult N. annulata, which likely represents a divergence in sensory functions based on the different resource cues responded to by males (sex pheromones) and females (host plant odours). This is a rare example of a study which quantifies variation in the numbers and dimensions of all antennal sensilla types for males and females to allow a thorough statistical assessment of sexual dimorphism in antennal sensory architecture.